Parametric optimization of deep-hole drilling on AISI 1045 steel and online tool condition monitoring using an accelerometer. Issue 16 (10th December 2018) - Arunkumar, N; Thanikasalam, A; Sankaranarayanan, V; Senthilkumar, E
ABSTRACT: This paper aims at investigating the effects of the deep-hole drilling parameters such as cutting speed ( V c ), feed rate (FR) ( F r ), and coolant pressure ( C p ) on the quality of the hole produced. The diameter and depth of the deep hole considered in the present work were 10 and 120 mm, respectively. In this study, hole quality was analyzed using surface roughness, cylindricity, and circularity characteristics. Coolant pressure and spindle speed play a vital role in determining the quality of the hole. During the drilling process, the fitness of the tool wear was observed by using an accelerometer. The experiments were conducted by varying the drilling parameters based on Taguchi's Design of Experiment, and the output responses were measured and optimized using grey relation analysis. The results indicate a yield of the better surface finish from higher spindle speed, lower circularity, and cylindricity. Also, the tool wear was reduced by decreasing spindle speed. Based on the grey relational technique, optimal process parameter settings were found such as spindle speed of 2228 rpm, FR of 0.023 mm/rev, and coolant pressure of 30 kgf/cm 2 .